A precarização na formação dos(as) pedagogos(as) no século XX: uma análise dos marcos legais para o curso de Pedagogia de 1939 a 1996 - Faustino, Heitor Henrique (2023)
The process of precarious work is a phenomenon that expands over the entirety of the social fabric, conditioning and being conditioned by numerous processes, among which we can mention the formation of subjects. Thus, we question whether it would also be possible to understand whether the process of precarious work can be identified in the legal frameworks for the Pedagogy course in the period from 1939 to 1996. To answer this question, we carried out a documentary research whose methodology was based on Discourse Analysis. We understand the phenomenon of precarious work as a condition established by capital for the working class to produce ever more, in objective, subjective and legal conditions that are increasingly deteriorated and deregulated, and receiving ever less from the sale of their workforce and/or the total amount of socially generated wealth, this condition manifests itself in different manners and forms, being articulated in the 20th century by the Taylorist-Fordist and Toyotist work management models. The results pointed to the existence of a tendency in the legislation for the Pedagogy course to follow the models of capitalist management, manifested mainly in the elements of specialization, fragmentation, polyvalence and flexibility, these elements and their unfolding during the historical development of the Pedagogy course and the work of this professional engender situations of precarious work whose aspects can still be identified in the education of the pedagogue.